Plant stem cell research is uncovering the secrets of longevity and persistent growth. (25th March 2021) - Umeda, Masaaki; Ikeuchi, Momoko; Ishikawa, Masaki; Ito, Toshiro; Nishihama, Ryuichi; Kyozuka, Junko; Torii, Keiko U.; Satake, Akiko; Goshima, Gohta; Sakakibara, Hitoshi
Summary: Plant stem cells have several extraordinary features: they are generated de novo during development and regeneration, maintain their pluripotency, and produce another stem cell niche in an orderly manner. This enables plants to survive for an extended period and to continuously make new organs, representing a clear difference in their developmental program from animals. To uncover regulatory principles governing plant stem cell characteristics, our research project 'Principles of pluripotent stem cells underlying plant vitality' was launched in 2017, supported by a Grant‐in‐Aid for Scientific Research on Innovative Areas from the Japanese government. Through a collaboration involving 28 research groups, we aim to identify key factors that trigger epigenetic reprogramming and global changes in gene networks, and thereby contribute to stem cell generation. Pluripotent stem cells in the shoot apical meristem are controlled by cytokinin and auxin, which also play a crucial role in terminating stem cell activity in the floral meristem; therefore, we are focusing on biosynthesis, metabolism, transport, perception, and signaling of these hormones. Besides, we are uncovering the mechanisms of asymmetric cell division and of stem cell death and replenishment under DNA stress, which will illuminate plant‐specific features in preserving stemness. Our technology support groups expand single‐cell omics to describe stem cell behavior in a spatiotemporal context, and provide correlative light and electron microscopic technology to enable live imaging of cell and subcellular dynamics at high spatiotemporal resolution. In this perspective, we discuss future directions of our ongoing projects and related research fields. Significance Statement: Plant stem cells are distinct from animal tissue stem cells in that they maintain pluripotency throughout life. Here we highlight achievements and future perspectives of our projects on stem cell research, including reprogramming, hormonal and epigenetic regulation of stemness, meristem determinacy, and the control of asymmetric division and genome integrity in plant stem cells.